2021
DOI: 10.4081/jphr.2021.2122
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice on Covid-19 among Students during the Early Phase of Pandemic in a University in Borneo, Malaysia

Abstract: Background: COVID-19 related knowledge, attitude and practice plays a major role in determining the readiness of the community to adopt the behavioural change towards recommended preventive measures outlined by public health officials. This study aims to assess the knowledge, attitude, and practice regarding COVID-19 among university students as well as its associated factors. Method: This is a cross sectional study that was conducted among students in a public university during the early phase of COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…This study found that most respondents had a negative attitude (61%). This result was similar to Sazali et al (2021), where most respondents had negative attitude scores regarding . This might be because of the adaptation of the new norm.…”
Section: Attitude Towards Handling Covid-19 Among Nurses In Ummcsupporting
confidence: 80%
“…This study found that most respondents had a negative attitude (61%). This result was similar to Sazali et al (2021), where most respondents had negative attitude scores regarding . This might be because of the adaptation of the new norm.…”
Section: Attitude Towards Handling Covid-19 Among Nurses In Ummcsupporting
confidence: 80%
“…Previous studies associated individuals with lower educational level having reduced COVID-19 knowledge 22,29 ; thus, making them more vulnerable and more likely to develop negative attitude and behaviour 22 .…”
Section: Asmentioning
confidence: 99%
“…In the Malaysian context, majority of the studies focused on general population including young adults and elderly 13,28 and university students 29 . Although, one recent study with a younger age group (15 years and above) aimed to find the KAP of social distancing during COVID-19 outbreak 30 .…”
Section: Asmentioning
confidence: 99%
“…The following are available online at https://www.mdpi.com/article/ 10.3390/bs11080106/s1, Text: Method (References[47][48][49][50][51][52][53][54][55][56][57][58][59][60]); TableS1: Demographic, education, and professional statistics of participants across different countries.Table S2: p-value for different Chi-Squared Test result with 95% significance. (Significant results are bold).…”
mentioning
confidence: 99%
“…The following are available online at , Text: Method (References [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]); Table S1: Demographic, education, and professional statistics of participants across different countries. Table S2: p-value for different Chi-Squared Test result with 95% significance.…”
mentioning
confidence: 99%